The Influence of Financial Ratio on Stock Price of LQ45 Index Companies Listed on Indonesia Stock Exchange - Teo Li Jin; Robinhot Gultom; Ella Silvana Ginting (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2022)
This study aims to determine and analyze the effect of financial ratios (Return on Equity, Earning Per Share, and Debt to Equity Ratio) simultaneously or partially on stock prices of LQ45 index companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The data analysis method used is the multiple linear regression method. The population in this study amounted to 62 companies and the number of samples obtained was 24 companies. The sampling method used a purposive sampling technique. Based on the results of data testing, it is known that simultaneously, Return on Equity, Earning Per Share, and Debt to Equity Ratio have a significant effect on stock prices of LQ45 index companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Partially, Earning Per Share has a significant positive effect on stock prices of LQ45 index companies listed on the Indonesia Stock Exchange for the 2018-2020 period. However, Return on Equity and Debt to Equity Ratio have a significant negative effect on stock prices in LQ45 index companies listed on the Indonesia Stock Exchange for the 2018-2020 period.